Textural characteristics of composite adsorbents analyzed with density functional theory and self-consistent regularization procedure - V. M. Gun'ko (Хімія, фізика та технологія поверхні, 2020)
Highly disperse or porous complex and hybrid materials and nanocomposites characterized by the presence of several phases, nonuniform particulate morphology, and complicated porosity with contributions of pores of various shapes are widely used in various applications in industry and medicine. Accurate determination of their textural characteristics is of importance from a practical point of view because these characteristics play an important role in practically all applications of the materials. The aim of this study, to solve the mentioned task, is to develop a self-consistent regularization (SCR) procedure applied to integral adsorption equations based on complex models with slit-shaped and cylindrical pores and voids between spherical particles packed in random aggregates (SCV model) for two or three types of components (such as activated carbon, carbon black, silica gel, and fumed silica) in composites, mechanically treated, with application of the density functional theory (DFT) method. The pore size distribution (PSD) functions calculated using the DFT SCV/SCR method are compared to the PSD calculated for the same materials with the SCV/SCR method based on the modified BET/Kelvin equations (MND method) previously developed. The DFT SCV/SCR method works better than the latter since it gives smaller model errors and better describes the PSD functions of composite components alone. The DFT SCV/SCR method could be used to study the textural characteristics of various complex and hybrid materials and composites which are characterized by a nonuniform porosity. It should be noted that the PSD functions of similar complex adsorbents are difficult to be calculated using standard approaches distributed with firm software due to restriction on the type of material (typically one) and the absence of SCR.